AI as a Speaking Partner: Exploring Students’ Experiences of Practicing English Conversations with Stimuler - Raden Viranty Kamilatul Fasa; Gisna Auliya; Andang Saehu; Cipto Wardoyo (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
Aimed to explore students' experience in using Artificial Intelligence (AI), particularly Stimuler, as a speaking partner in practicing conversation using English. The study is grounded in the limited opportunities for speaking practice, such as the low confidence and anxiety commonly experienced by EFL students. This study employed a qualitative descriptive method involving four students who were selected through purposive sampling from various majors. The data from this study were collected through semi-structured interviews and analyzed using thematic analysis. The study shows that using AI, specifically Stimuler, as a speaking partner offers several benefits, as reflected in the themes: AI as a Safe and Low-Anxiety Speaking Environment, Enhancing Students' Speaking Development, and Flexibility and Accessibility of AI-Based Learning. However, there are also limitations, especially in natural interaction and its limitations in replacing humans in conversation. All in all, it shows that Stimuler can be an effective speaking partner for some students to improve their speaking skills, by creating a practice space that is flexible and less pressurizing.